Analisis Soal Ujian Semester Ganjil Mata Pelajaran Sejarah Indonesia Kelas X SMAN di Kota Padang Menggunakan Program AnBuso 8.0 - Rizki Oktavian; Ofianto Ofianto (RC-INSTITUT, 2019)
This research aims to determine the quality of the item odd Final Exam Subjects Indonesian History Class X SMAN in Padang Year 2018/2019 the terms of validity, reliability, level of difficulty, distinguishing features and analysis of detractors. This research was quantitative descriptive. Subjects in this research were students of 2 class x SMAN 3 Padang, 2 class x SMAN 7 Padang and 2 class x SMAN 12 Padang. Data was collected by the documentation method. Data were analyzed using the program AnBuso 8.0 and manual calculations with the helped of the Excel program. The results of this research were Quality items based on the total analysis items about the excellent for package 1 good quality about 16 items or 32%, poor quality were 32 items or 64%, and not very good quality amounted to 2 items or 4%. Whereas for package 2 good quality about 16 items or 58%, poor quality were 29 items or 64%, and not very good quality amounted to 5 items or 10%.